ISLAMIC ECONOMIC REVIEW ON THE IMPLEMENTATION OF MUDHARABAH MUTHLAQOH AGREEMENTS IN INDONESIAN HAJJ SAVINGS PRODUCTS AT BSI (BANK SYARIAH INDONESIA) M. KHOLIL BANGKALAN BRANCH - Rasidi, Yusuf Pandu; Hasan, Dony Burhan Noor (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Abstract: The research with the title "Islamic Economic Overview of the Implementation of Mudharabah Muthlaqoh Agreements in Indonesian Hajj Savings Products at BSI (Bank Syariah Indonesia) M. Kholil Bangkalan Branch" has the aim of finding out how the contracts contained in Hajj savings products at BSI Bangkalan are implemented which will later be analyzed with Islamic economic theory. In this research, descriptive research is applied using a qualitative approach, and the method used to collect data is in the form of interviews and documentation, the data analysis method applies descriptive qualitative analysis. The results of the research show that in accordance with the pillars and conditions, namely for people who carry out contracts, namely capital owners and capital managers, it is implied that they must be competent to act. Mudarabah is absolute, capital owners do not bind property managers to trade in certain countries, trade certain goods and at certain times. The capital or goods handed over are in the form of cash which acts as a transaction tool in a country. It has been implemented well and in accordance with existing administration. The profits obtained are only intended for the party entering into the agreement. The percentage distribution of profits that will belong to the manager and capital owners must be clear according to the agreement, for example half, one third, or one quarter. Ijab and kabul are carried out with clear and implied shi'gat accompanied by stating the distribution of profits firmly and clearly. If it is not stated clearly then the contract is invalid. This has also been stated in the agreement file which was agreed at the beginning when carrying out transactions at BSI Bangkalan between the customer and BSI. So overall the requirements in Islamic economics regarding the implementation of mudharabah contracts have been implemented well. So the researcher can conclude that BSI Bangkalan is in accordance with Islamic economics in implementing the mudharabah muthlaqoh agreement on Hajj savings products. Keywords:Mudharabah Muthlaqoh, Hajj Savings, Islamic Economics